Patient safety at risk: non compliance with drug regulations among community pharmacies in Chennai, Tamil Nadu - S., Prabakaran; S. G., Santhoshkumar; S. U., Deepika; T., Vishnu; Mohanta, Guru Prasad (International Journal Of Community Medicine And Public Health, 2025)
Background: Over-the-counter (OTC) drugs are available for consumer purchase without prescriptions, whereas Schedule H medications require valid prescriptions from registered medical practitioners. This pilot study assesses the dispensing practices of community pharmacists in Chennai using the simulated client method. Methods: Two Pharm.D. students, trained to role-play as simulated clients, visited 25 community pharmacies in Chennai to request Tab. Prednisolone 40 mg. Each interaction was documented using a data collection form focusing on control, compliance, and complications. Data were analyzed using descriptive statistics and Chi-square tests. Results: Out of 25 pharmacies, 52% agreed to dispense the medication without justification, while 44% strongly disagreed even after explanations were provided. Only 36% asked for a prescription, and a concerning 64% did not prioritize its necessity. Only 12% of respondents provided information about the medication, with location statistically significant in relation to prescription requests (p=0.027). Notably, two pharmacies allowed unqualified personnel to dispense medications. Conclusions: The pilot study reveals inappropriate practices among community pharmacists in Chennai, emphasizing the urgent need for awareness programs and regulatory revisions. The high rates of non-compliance raise concerns about patient safety and highlight the necessity for strategic public health initiatives similar to Kerala’s Operation AMRITH. Immediate action is essential to improve pharmacy practice standards and ensure safe dispensing of medications.